The political economy of Mangifera indica The case of Guimaras Mango industry. - Sacramento, Noe John Joseph
The study of political economy is important in order to determine the issues that are present in the capitalist system. It has been identified that labor exploitation will always exist within the capitalist system unless it would be addressed. The emergence of the Guimaras mango industry as a driver for the success in the economy of the province also marked the heightening of labor exploitation within the industry. The main objectives of this study are (a) to identify the socio-economic condition of mango famers and workers in selected mango yards, orchards, and processing factories in Guimaras (b) to describe the labor conditions of farmers and workers in the cycle of mango production and (c) to analyze the labor relation in the production and processing of mango as a domestic and international export commodity. Although the mango industry provides jobs for the Guimarasnons, it does not guarantee that the welfare of the laborers is protected. It cannot be considered as the primary source of income because of the factors that make it as unreliable source of income. The domination of the capitalist is evident as characterized by the low wages and ill-compensation of the laborers. All benefits from their products of labor go to the capitalists despite the fact that without their labor, value will not be attained. The laborers are the drivers of the industry, without them, the industry will never succeed. The role of the laborers is vital within the industry but measures by the government to protect their welfare are still lacking. The exploitation of the laborers continues to persist despite their contribution in the industry because their importance is being recognized. The mango industry will not succeed without the mango laborers and factory workers. This study explores the evidences provided by the mango laborers and factory workers interviewed as well as by different data from institutions concerned with mango industry.